Characterization of crystal water molecules in a high-affinity inhibitor and hematopoietic prostaglandin D synthase complex by interaction energy studies. Issue 16 (1st September 2018) - Takaya, Daisuke; Inaka, Koji; Omura, Akifumi; Takenuki, Kenji; Kawanishi, Masashi; Yabuki, Yukako; Nakagawa, Yukari; Tsuganezawa, Keiko; Ogawa, Naoko; Watanabe, Chiduru; Honma, Teruki; Aritake, Kosuke; et al.
Graphical abstract: Abstract: Hematopoietic prostaglandin D synthase (H-PGDS) is one of the two enzymes that catalyze prostaglandin D2 synthesis and a potential therapeutic target of allergic and inflammatory responses. To reveal key molecular interactions between a high-affinity ligand and H-PGDS, we designed and synthesized a potent new inhibitor (KD : 0.14 nM), determined the crystal structure in complex with human H-PGDS, and quantitatively analyzed the ligand–protein interactions by the fragment molecular orbital calculation method. In the cavity, 10 water molecules were identified, and the interaction energy calculation indicated their stable binding to the surface amino acids in the cavity. Among them, 6 water molecules locating from the deep inner cavity to the peripheral part of the cavity contributed directly to the ligand binding by forming hydrogen bonding interactions. Arg12, Gly13, Gln36, Asp96, Trp104, Lys112 and an essential co-factor glutathione also had strong interactions with the ligand. A strong repulsive interaction between Leu199 and the ligand was canceled out by forming a hydrogen bonding network with the adjacent conserved water molecule. Our quantitative studies including crystal water molecules explained that compounds with an elongated backbone structure to fit from the deep inner cavity to the peripheral part of the cavity would have strong affinity to human H-PGDS.